Influence of gadolinium and annealing time in dysprosium doped oxyfluoride glasses for w-LED and scintillating photonic device applications - R. Rajaramakrishna; J. Kaewkhao; N.V. Nikonorov; E. Aleksandrova; S. Kothan; W. Busayaporn; S. Rahul; M.A. Gerasimova; E.A. Slyusareva (Next Materials)
The influential behavior of the dysprosium luminescence intensity was observed based on the oxidation state of the gadolinium ions inside the glass matrix. The highest luminescence intensity was observed for the un-treated ceria samples and compared without ceria content glass sample. Decreasing luminescence intensity with increase in annealing time was noticed for ceria-based glasses. XANES analysis was performed to understand the oxidation state of the glasses. X-Ray luminescence confirms their scintillating behavior and shows a similar trend as observed in photoluminescence. Asymmetry ratio of these glasses has been evaluated and found to be greater than unity. We have evaluated the highest photoluminescence quantum yield, which shows 19% when excited at a wavelength of 452 nm.